Development of a hybrid solar thermal system with TEG and PEM electrolyzer for hydrogen and power production - Demir, Murat Emre; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, a hybrid system for electricity and hydrogen (H-2) production is proposed and analyzed thermodynamically. The proposed system consists of a concentrated solar powered gas turbine subsystem, a latent heat storage subsystem, a multi-stage flash distillation (MFD) subsystem, a proton exchange membrane (PEM) electrolyzer and a thermoelectric generator (TEG). In the present system, the pressurized hot air by the solar receiver runs the gas turbine, and hence the electricity is generated. The exhaust heat of the gas turbine charges the latent heat storage system which uses NaOH and 60Mg-25Cu-15Zn as the phase change material (PCM). The MFD produces fresh water from seawater. The seawater utilized in the MFD is heated by the PCM. The PEM electrolyzer produces the H-2 and O-2 from the distilled water. The TEG unit is used for recovering the waste heat of the gas turbine. Bi2Te3 and Bi2Te2Se1 are selected as the thermoelectric material for the TEG. The COMSOL Multiphysics software package is used for numerical modeling the TEG, and the rest of the components of the integrated system is analyzed in the Engineering Equation Solver (EES). The overall energy and exergy efficiencies of each system component are determined, and H-2, fresh-water, electric power generation capacity of the system are then calculated. Furthermore, the effects of direct normal irradiance (DNI) level, the wind speed and the operating temperature of the PEM electrolyzer on the system performance are investigated. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Solar energy; Electrolysis; Desalination; Energy; Exergy; PHASE-CHANGE MATERIALS; ENERGY-STORAGE; RENEWABLE ENERGY; THERMOELECTRIC GENERATOR; FUEL-CELL; HEAT; DESIGN; ANKARA; Chemistry; Electrochemistry; Energy & Fuels